2016
DOI: 10.1177/2333393616670212
|View full text |Cite
|
Sign up to set email alerts
|

Birth Care Providers’ Experiences and Practices in a Brazilian Alongside Midwifery Unit

Abstract: The implementation of a new birthing facility in a country such as Brazil requires an extensive in-depth analysis of the challenges faced. The aim of this study was to explore beliefs, values, experiences, and practices related to the provision of birthing and neonatal care with the implementation of a new birth care facility structure called alongside midwifery units in Brazil. The study utilizes an ethnographic method to evaluate members of a Brazilian public hospital’s midwifery unit. The ethnographic study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 28 publications
0
17
0
1
Order By: Relevance
“…Nurses and midwives expressed difficulty in maintaining privacy during vaginal examinations and delivery due to the absence of screens and overcrowding. Similar studies across low‐income countries have reported several violations of women's privacy and attributed it to poor hospital infrastructure, overcrowding and lack of resources such as screens and partitions (Macdonald et al, 2019; Mselle et al, 2018; Munabi‐Babigumira et al, 2019; Narchi et al, 2017; Nunes et al, 2016).…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Nurses and midwives expressed difficulty in maintaining privacy during vaginal examinations and delivery due to the absence of screens and overcrowding. Similar studies across low‐income countries have reported several violations of women's privacy and attributed it to poor hospital infrastructure, overcrowding and lack of resources such as screens and partitions (Macdonald et al, 2019; Mselle et al, 2018; Munabi‐Babigumira et al, 2019; Narchi et al, 2017; Nunes et al, 2016).…”
Section: Discussionmentioning
confidence: 84%
“…Narrative of frequent shortages of delivery kits, oxygen, intravenous fluid, oxytocic agents, blood products, resuscitation kits, beds, and malfunctioning equipment was reported to significantly constrained the delivery of care to childbearing women (Adolphson et al, 2016; Boakye et al, 2021; Macdonald et al, 2019; Mothiba et al, 2019; Mselle et al, 2013; Munabi‐Babigumira et al, 2019; Nabirye et al, 2014; Uwajeneza et al, 2015). Others described inadequate spacing and poor infrastructure created precarious working conditions and overcrowding, thereby compromising the delivery of humanized care (Macdonald et al, 2019; Mselle, Kohi, & Dol, 2018; Munabi‐Babigumira et al, 2019; Narchi et al, 2017; Nunes et al, 2016). Maintaining a safe and ethical practice in the face of profound shortage of medical supplies and health personnel may undermine the moral agency and generate ethical dilemmas for midwives.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…of items of peer-reviewed literature (references) No. of items of grey literature (references) Survey indicated MLBC(s) Strong evidence (from two or three of the data source types) Afghanistan n=2 ( Jobs.Af, 2021 ; Summers, 2021 ) Bangladesh n=2 ( Mahmood et al., 2019 ; Wallace, 2019 ) n=6 ( Amin et al., 2020 ; Begum, 2019 ; Every Mother Counts, 2022 ; Goodbirth.net, 2021 ; Jahan, 2018 ; Michel-Schuldt et al., 2020a ) Brazil n=10 ( Caldas Nicacio et al., 2016 ; da Silva et al., 2013 ; 2012 ; Freitas et al., 2019 ; Nunes et al., 2016 ; Progianti et al., 2013 ; Rodrigues Duarte et al., 2019 ; Santos et al., 2015 ; Schneck et al., 2012 ; Viana et al., 2012 ) n=2 ( Goodbirth.net, 2021 ; Silva, 2019 ) nr Ecuador n=2 ( Goodbirth.net, 2021 ; New Life Ecuador, 2020 ) Fiji n=2 ( United Nations Population Fund, 2019 ; Vula, 2018 ) Gambia n=2 ( Sheikh Tihami I Nyass Foundation, 2022 ; Tripadvisor, 2015 ) Ghana n=2 ( Goodbirth.net, 2021 ; United Nations Population Fund, 2021b ) ...…”
Section: Resultsmentioning
confidence: 99%
“…Pesquisas brasileiras documentaram tal violência 22 por meio de procedimentos não explicados e não autorizados (27,3%) 23 , recusa de permissão para acompanhantes (9,3%) [24][25] , e elevada taxa de cesarianas e nascimentos prematuros 26 , registrando o impacto na saúde de indivíduos, famílias, comunidades e sociedades 25 . O ativismo político latino-americano, com destaque ao movimento brasileiro de humanização do parto, ainda é insuficiente para coibir tal violência 27 .…”
Section: Revisão De Literaturaunclassified